ASPECTS OF USING TRANSDENTAL IMPLANTS IN CONSERVATIVE AND OPERATIVE DENTAL SURGERY (Conferencea, 2022)
In recent years, all over the world, much attention has been paid to the widespread introduction of tooth-preserving operations performed on an outpatient basis. The arsenal of these operations includes well-known methods of cystectomy with resection of the root tips, hemisection, amputation of the roots of the teeth and coronary radicular separation. However, doctors rarely use these operations and often extract teeth even in cases where it is possible to save them. At the same time, the preservation of such teeth, even with reduced resistance, has undoubted advantages both from an economic point of view and from the point of view of the prospects for the functional results of treatment.